THE COURT SYSTEM SUPPLY CHAIN AND ITS DYNAMICS – A CASE STUDY - Martins, A.; Crespo de Carvalho, J. (9th International Symposium on Logistics, 2004)
The Portuguese court system verifies longer cycle times then expected. The purpose of this paper is to determine the ability to approach the Portuguese court system as a dynamic supply chain and discuss its dynamics so that reduced cycle times are achieved. System dynamics theory and a supply chain approach will be used. A case study is analysed in order to identify areas of improvement. Findings confirm the purpose and identify topics for reduction of court cases cycle time. Limitations and topics for further research are also identified.